2016
DOI: 10.1080/19443994.2014.989269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic strength on the adsorption behavior of phenol over modified activated clay

Abstract: 2014): Effect of ionic strength on the adsorption behavior of phenol over modified activated clay, Desalination and Water Treatment, In this paper, the effect of several inorganic salts (NaCl, KCl, MgCl 2 , ZnCl 2 , Na 2 SO 4 , Na 3 PO 4 ) on phenol adsorption at different ionic strength by cetyl trimethyl ammonium bromide and CaO modified activated clay was studied. The adsorption isotherm, adsorption kinetics and thermodynamic in the presence of NaCl were also investigated. The results showed that phenol rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…As a result, the removal rate of RG-19 dye is decreasing. 40 This investigation is supporting the strong contribution of electrostatic interaction mechanism of this adsorption process. On the other hands, the increasing of ionic strength leads to the decreasing the removal e ciency of RG-19 dye that mainly because the increasing of pH.…”
Section: Removal Of Rg-19 Dye By Flasupporting
confidence: 69%
“…As a result, the removal rate of RG-19 dye is decreasing. 40 This investigation is supporting the strong contribution of electrostatic interaction mechanism of this adsorption process. On the other hands, the increasing of ionic strength leads to the decreasing the removal e ciency of RG-19 dye that mainly because the increasing of pH.…”
Section: Removal Of Rg-19 Dye By Flasupporting
confidence: 69%
“…This indicated that the process was more spontaneous at higher temperature. While the positive (∆H°) and (∆S°) an indication that (MV) adsorption on B and B-SDS is a endothermic and randomized process [34].…”
Section: Thermodynamic Parametersmentioning
confidence: 95%
“…The authors [27] also had similar results when methylene blue removed decreased from 81.5 to 14 mg/g when the ionic strength increased from 0.00 to 0.1 M using orange peel as an adsorbent. The presence of salts in solution blocks the active sites of the adsorbents thereby preventing the RB molecules from attaching to the surface, hence reducing the removal efficiency [27,28] (Table 5).…”
Section: Influence Of Ionic Strength On Rb Removalmentioning
confidence: 99%